Accumulated decoupled learning with gradient staleness mitigation for convolutional neural networks - Zhuang, Huiping (2024)
Gradient staleness is a major side effect in decoupled learning when training convolutional neural networks asynchronously. Existing methods that ignore this effect might result in reduced generalization and even divergence. In this paper, we propose an accumulated decoupled learning (ADL), which includes a module-wise gradient accumulation in order to mitigate the gradient staleness. Unlike prior arts ignoring the gradient staleness, we quantify the staleness in such a way that its mitigation can be quantitatively visualized. As a new learning scheme, the proposed ADL is theoretically shown to converge to critical points in spite of its asynchronism. Extensive experiments on CIFAR-10 and ImageNet datasets are conducted, demonstrating that ADL gives promising generalization results while the state-of-theart methods experience reduced generalization and divergence. In addition, our ADL is shown to have the fastest training speed among the compared methods. The code will be ready soon in https://github.com/ZHUANGHP/Accumulated- Decoupled-Learning.git.